(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2023)
Background:Hanging is a form of asphyxia caused by external pressure on upper airwaysderived from a band tightened by the gravitational weight of the body. It could by suicidal or homicidal. Method: 50 dead bodies (35 males and 15 females) aged between 20-70 years old who died due to hanging were studied. The autopsies were carried out to rule out genderdifferences,pattern ofligature marks on neck, ligature material used, fractures of hyoid bone or thyroid cartilage in the neck, significant findings in dissection of neck caused by death due to hanging, differences between antemortemand postmortem hanging, associated injuries in hanging etc. Results: 35 (70%) males, 15 (30%) females dead bodies due to hanging 19 (38%) were summer, 20 (40%) in rainy, 11 (22%) in winter season, 14 (28%) outdoor, 36 (72%) were outdoor hanging deaths, 36 (72%) ligatures were above the thyroid cartilage, 9 (18%) at the level of cartilage, 5 (10%) below the level of thyroid cartilage. The significant findings of neck dissection were 30 (60%) in the present study. Conclusion: The present study of deaths due to hanging will certainly help the medico-legal experts to differentiate betweensuicidalandhomicidal hanging.